2008
DOI: 10.1183/09031936.00056008
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography assessment of lung volume changes after bronchial valve treatment

Abstract: The aim of the present study was to correlate clinical outcome measures following treatment with bronchial valves with regional lung volume. Computed tomography (CT) scan data from 57 subjects with severe emphysema were obtained from nine North American clinical trial sites. IBV1 Valves (Spiration, Inc., Redmond, WA, USA) were placed to occlude segmental and subsegmental bronchi in right and left upper lobes using a flexible bronchoscope. Subjects completed a St George's Respiratory Questionnaire (SGRQ), pulmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
91
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(100 citation statements)
references
References 31 publications
7
91
2
Order By: Relevance
“…7,8 These measures are commonly reported in clinical investigation and have been shown to correlate with spirometric and clinical measures of disease. [9][10][11][12] Little attention has been paid, however, to using chest CT scans to determine the normal range of lobe volumes at full infl ation and relaxed exhalation. Once such models have been developed, investigators could then determine the absolute amount of lobe-specifi c hyperinfl ation present on the inspiratory scan (ie, how much lobe volume exceeds predicted at full infl ation) and the lobe-specifi c volume of gas trapped on an expiratory CT image.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 These measures are commonly reported in clinical investigation and have been shown to correlate with spirometric and clinical measures of disease. [9][10][11][12] Little attention has been paid, however, to using chest CT scans to determine the normal range of lobe volumes at full infl ation and relaxed exhalation. Once such models have been developed, investigators could then determine the absolute amount of lobe-specifi c hyperinfl ation present on the inspiratory scan (ie, how much lobe volume exceeds predicted at full infl ation) and the lobe-specifi c volume of gas trapped on an expiratory CT image.…”
Section: Discussionmentioning
confidence: 99%
“…In 57 subjects treated with the Spiration valve, CT measurements of atelectasis and volume reduction before and after treatment were correlated with symptomatic response. However, this was not correlated with improvements in pulmonary function tests [145].…”
Section: Update On Copdmentioning
confidence: 69%
“…CT examinations performed following valve implantations have shown that the desired atelectasis is frequently not achieved, can have a delayed onset or is only temporary [51]. The main reason for this would be what is referred to as collateral ventilation (CV), i. e. even if the valves are placed correctly and good occlusion is established, a retrograde reventilation of the treated lobe occurs via parenchymal bridges from the neighboring lobe [52].…”
Section: Fissure Analysis: the Interlobular Fissuresmentioning
confidence: 99%